Luminescent characteristics of Dy3+-doped polymethyl methacrylates for white light-emitting diode - Xiaobin Ren (Results in Physics, 2018)
To explore white-light-emitting materials, a series of Dy3+-doped polymethyl methacrylate (PMMA) samples are prepared by polymerization method. Excitation spectra and emission spectra are experimentally investigated. It is found that the luminous color of the PMMA sample doped with 0.1 mol% Dy3+ ion is white to the naked eye under 326 nm excitation. The CIE chromaticity coordinates (X = 0.321, Y = 0.336) of the emission are close to the standard white-light illumination (0.333, 0.333). The results are helpful in developing luminescent materials aimed for white light-emitting diodes. Keywords: Luminescence, Optical materials and properties, Rare-earth ions